The Role of International University Associations in the Development of Inter-Institutional Relations - S. S. Lachininskii; K. A. Morachevskaya; A. S. Zinovyev; I. S. Sorokin (Евразийская интеграция: экономика, право, политика, 2019)
The paper deals with the information on current inter-university associations, the principles of their organization and functioning. The typology of university associations according to the purposes of creation was designed. The types included associations to enhance regional integration in the field of education; associations to improve the quality of education in a particular subject area; association for joint lobbying before the challenges of today’s globalized world; association for the development of educational and research activities in a particular subject area; association for the establishment and promotion of joint educational programs on the network principle; association for the development of inter-university mobility of students and teachers. In conclusion, the role of such structures in the development of inter-university relations was formulated.